Protein Binding Characteristics of the Principal Green Tea Catechins: A QCM Study Comparing Crude Extract to Pure EGCG - Elsadig E. Ali; Mohamed O. Elmakki; Miranda L. Gavette; Brian J. Doyle; Shannon J. Timpe (Biochemistry Research International)
Label-free detection methods such as the quartz crystal microbalance (QCM) are well suited to the analysis of molecular interactions in complex mixtures such as crude botanical extracts. In the present study, the binding characteristics of epigallocatechin gallate (EGCG) and crude green tea extract solutions to bovine serum albumin (BSA) have been investigated. The adsorbed mass levels onto BSA-functionalized surfaces were measured at various solution concentrations. Langmuir and Freundlich isotherms were used to model the adsorption data. The Langmuir isotherm better described the adsorption behavior with correlations of 0.68 and 0.70 for the EGCG and the crude extract solutions, respectively. The better fit of the Langmuir model indicates that adsorption occurs homogeneously and that aggregation is negligible. The mass saturation is estimated to be 58% higher for the crude green tea solution as compared to the pure EGCG solution (7.9 ng/cm2 for green tea and 5 ng/cm2 for EGCG). The increased adsorption for the crude extract indicates that the additional tea chemical constituents are binding to alternate sites on the protein molecule and that competitive binding is a nondominant effect. However, a reduced adsorption rate for the crude extract was also observed, indicating some presence of competitive mechanisms. The results demonstrate the utility of the QCM for the analysis of protein binding in crude mixtures as well as pure compounds.